2021
DOI: 10.33805/2641-7383.127
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Wood Ash, Turbulence, and Traps with Excess of Sulfuric Acid Do Not Strip Completely the Ammonia off an Agro-waste Digestate

Abstract: The present study combined two nutrient management strategies to improve the marketability of a waste-derived fertilizer: (a) isolation of ammoniacal nitrogen and (b) preparation of a bulk soil amendment. The wood fly ash with low content of pollutants was added to an agrowaste anaerobic digestate as alkaline stabilizer, which promoted the volatilization of ammonia and adsorption processes, and as nutrient supplement. The 39.71 ± 1.44 g blend was incubated for 60 hours at 20°C and 100 rpm in a closed chamber (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A benefit of this methodology, compared to the closed chamber, is that it allows quantification of the emissions of NH 3 and CO 2 with titrations of the brine because, unlike the pH of the H 2 SO 4 solution, the pH of the brine does change considerably due to the absorption of NH 3 and CO 2 , which makes possible to avoid specialized analytical equipment (e.g., Autoanalyzer segmented flow colorimetry or Total Nitrogen machine). Interestingly, the absorption of NH 3 in H 2 SO 4 solution implies, as in the brine of the anhydrous salt, a decrease in pH (Moure Abelenda et al, 2021a), due to the formation of the acidic salt (NH 4 ) 2 SO 4 , similarly to the developed artifact, which stores the NH 3 as NH 4 Cl and decreases the pH. The range of pH of the CaCl 2 brine is more suitable to detect low amounts of NH 3 absorbed in the liquid, compared to the very low pH of the acid H 2 SO 4 solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A benefit of this methodology, compared to the closed chamber, is that it allows quantification of the emissions of NH 3 and CO 2 with titrations of the brine because, unlike the pH of the H 2 SO 4 solution, the pH of the brine does change considerably due to the absorption of NH 3 and CO 2 , which makes possible to avoid specialized analytical equipment (e.g., Autoanalyzer segmented flow colorimetry or Total Nitrogen machine). Interestingly, the absorption of NH 3 in H 2 SO 4 solution implies, as in the brine of the anhydrous salt, a decrease in pH (Moure Abelenda et al, 2021a), due to the formation of the acidic salt (NH 4 ) 2 SO 4 , similarly to the developed artifact, which stores the NH 3 as NH 4 Cl and decreases the pH. The range of pH of the CaCl 2 brine is more suitable to detect low amounts of NH 3 absorbed in the liquid, compared to the very low pH of the acid H 2 SO 4 solutions.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous investigation, the initial pH of 10-mL solutions of H 2 SO 4 (with concentrations ranging from 0.1 to 1 M) placed in the trap of the closed chamber method was 0.92 ± 0.005. Due to the absorption of NH 3 released from the incubation of 3.22 ± 1.43 g of whole agrowaste anaerobic digestate (AWD) at pH 10.40 ± 0.46 for 60 h at 100 rpm at 20°C, the pH of the H 2 SO 4 solutions decreased 0.25 ± 0.02 units (Moure Abelenda et al, 2021a). Assuming that all the NH 3 released ended in the H 2 SO 4 trap, the rates of volatilization were: et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a mild dose of wood ash can be used without open-loop acidification (i.e., without using commercial acids: H 2 SO 4 , HCl, HNO 3 , and CH 3 CH(OH)COOH) to achieve the pH zpc by means of NH 3 volatilization (i.e., noninvasive acidification; Equation (2)). Nevertheless, the implementation of a method to recover the NH 4 + -N is required, such as absorption of the NH 3 volatilized into a H 2 SO 4 solution [90,91]. In fact, this is a route for the valorization of the anaerobic digestate and production of a mineral-grade fertilizer [66], which can be marketed as a 40-60% ammonium sulfate solution [64] or as pure crystals of (NH 4 ) 2 SO 4 [92].…”
Section: Discussionmentioning
confidence: 99%
“…This macronutrient has a relatively high total concentration in fly ash. Many studies have suggested that P in fly ash may not be available to plants [60]. Phosphorus is largely fixed with Fe and Al; this conglomerate is generally unavailable to plants [61].…”
Section: P K Mgmentioning
confidence: 99%